Tumor cell death in orthotopic breast cancer model by NanoALA: a novel perspective on photodynamic therapy in oncology - Andrade, Laise R. de; Tedesco, Antonio C.; Primo, Fernando L. [UNESP]; Farias, Gabriel R.; Silva, Jaqueline R. da; Longo, Joao P. F.; Almeida, Marcos C. de; Souza, Paulo E. N. de; Azevedo, Ricardo B. de; Pinheiro, Willie O.; Lacava, Zulmira G. M. (Future Medicine Ltd, 2020)
Aim: Nano-5-aminolevulic acid (NanoALA)-mediated photodynamic therapy (PDT), an oil-in-water polymeric nanoemulsion of ALA, was evaluated in a murine model of breast cancer. Materials & methods: Analysis of ALA-derived protoporphyrin IX production and acute toxicity test, biocompatibility and treatment efficacy, and long-term effect of NanoALA-PDT on tumor progression were performed. Results: The nanoformulation favored the prodrug uptake by tumor cells in a shorter time (1.5 h). As a result, the adverse effects were negligible and the response rates for primary mammary tumor control were significantly improved. Tumor progression was slower after NanoALA-PDT treatment, providing longer survival. Conclusion: NanoALA is a good proactive drug candidate for PDT against cancer potentially applied as adjuvant/neoadjuvant intervention strategy for breast cancer.
Keywords: 4T1 cells; 5-aminolevulinic acid; breast cancer; photodynamic therapy; polymeric nanoemulsion